2022
DOI: 10.3390/pharmaceutics14030517
|View full text |Cite
|
Sign up to set email alerts
|

Vardenafil Oral Dispersible Films (ODFs) with Advanced Dissolution, Palatability, and Bioavailability

Abstract: Oral, quick response, and on demand, also known as a spontaneous oral treatment for erectile dysfunction, is highly needed by both patients and physicians. Vardenafil is selective (fewer side effects) and more effective in difficult-to-treat conditions than sildenafil. This study aims at fostering the dual objectives of using biomolecules such as artificial sweetening agents to solubilize and mask the bitterness of vardenafil loaded on biodegradable polymeric materials (PVA, MC, SA, and PVP K30) to fabricate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Thermal properties of VDF, SPC, CHOL, SDC, and optimized VDF-loaded bilosomal formulation were recorded utilizing differential scanning calorimeter ( Figure 5 ). The pure vardenafil (VDF) thermogram exhibited a broad endothermic peak from 50–100 °C, corresponding to water loss, and another characteristic endothermic peak at 118 °C, corresponding to VDF melting [ 34 ]. The SPC thermogram showed an endothermic peak at 167 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal properties of VDF, SPC, CHOL, SDC, and optimized VDF-loaded bilosomal formulation were recorded utilizing differential scanning calorimeter ( Figure 5 ). The pure vardenafil (VDF) thermogram exhibited a broad endothermic peak from 50–100 °C, corresponding to water loss, and another characteristic endothermic peak at 118 °C, corresponding to VDF melting [ 34 ]. The SPC thermogram showed an endothermic peak at 167 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Another critical issue is the bitter taste of many APIs since the dosage form is in direct contact with the oral mucosa. The taste masking effect of APIs may be achieved through a variety of methods and technologies, such as the simple addition of flavour and sweetener combinations [ 72 , 73 ] or more complex systems such as drug complexation with ion exchange resins [ 74 ] or cyclodextrins [ 75 ].…”
Section: Limitations Of Odf’smentioning
confidence: 99%
“…The components PUL (X 1 ), MTX (X 2 ), and PG (X 3 ) had a substantial effect on the response TS (Y 3 ). Based on the findings of the ANOVA, a statistical model was developed to outline a workable relationship between the dependent and independent variables.The response Y 3 (TS, MPa) model produced a final equation regarding coded factors and responses, as shown in Equation (9).…”
Section: Tensile Strength (Ts) Analysismentioning
confidence: 99%
“…In recent decades, many studies have demonstrated that oral dispersible films (ODFs) as drug delivery systems (DDS) can provide a rapid onset of therapeutic effects and maximize drug bioavailability. ODFs are conventionally made by solvent casting method (SCM) or hot-melt extrusion (HME) using hydrophilic polymers [9]. Europe has already commercialized RIZAPORT ® ODFs prepared by SCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation